Relative shaft displacement and vibration measurements for the early fault detection in rolling element bearing - Leo, Sing Lim. (Universiti Malaysia Sarawak, UNIMAS, 2004)
In this research, vibrations caused by the good and faulty bearing for both categories of bearings were analysed. Experimental data from the relative shaft displacement measurements due to dynamic vibrations of the shaft were analysed using time waveform analysis to detect the sudden changes in amplitude as a function of time.